Identifikasi Segmentasi Pasar Properti Hunian di Wilayah Kabupaten Sleman - Pramana, A.Yunastiawan Eka; Fanani, Fahril (Institut Teknologi Nasional Yogyakarta, 2024)
Understanding the characteristics of the land and property market within an urban setting is crucial for urban planners. In Indonesian urban areas, where individual land ownership is predominant, it is essential to recognize how individual decisions accumulate and shape the city. One significant market force influencing urban development is the housing market. This market is highly segmented, so grasping the characteristics of housing market segmentation can help policymakers and urban planners create more effective urban policies. This research aims to identify the characteristics of housing market segmentation in Sleman Regency. Located adjacent to Yogyakarta City, which is a mid-sized city known for its educational and tourism activities, Sleman Regency has experienced significant growth in housing properties. By utilizing data collected from property listing websites, this research will explore the formation of housing segmentation in the studied area. Exploratory Spatial Distribution Analysis (ESDA) will be employed to examine the spatial distribution of housing properties based on value and size. The results may reveal the existence of housing property segmentation in the case study area, which can extend beyond the defined administrative boundaries. Additionally, the findings highlight the importance of proximity to the city center and the main university campus as key factors influencing housing location choices in the area.